Release of airborne particles and Ag and Zn compounds from nanotechnology-enabled consumer sprays: Implications for inhalation exposure - Calderon,L; Han,TT; McGilvery,CM; Yang,L; Subramaniam,P; Lee,K-B; Schwander,S; Tetley,TD; Georgopoulos,PG; Ryan,M; Porter,AE; Smith,R; et al. (ATMOSPHERIC ENVIRONMENT, 2017)
The increasing prevalence and use of nanotechnology-enabled consumer products have increased potential consumer exposures to nanoparticles; however, there is still a lack of data characterizing such consumer exposure. The research reported here investigated near-field airborne exposures due to the use of 13 silver (Ag)-based and 5 zinc (Zn)-based consumer sprays. The products were sprayed into a specially designed glove box, and all products were applied with equal spraying duration and frequency. Size distribution and concentration of the released particles were assessed using a Scanning Mobility Particle Sizer and an Aerodynamic Particle Sizer. Inductively coupled plasma mass spectrometry (ICP-MS) was used to investigate the presence of metals in all investigated products. Spray liquids and airborne particles from select products were examined using transmission electron microscopy (TEM) and Energy Dispersive X-ray Spectroscopy (EDS). We found that all sprays produced airborne particles ranging in size from nano-sized particles (<100 nm) to coarse particles (>2.5 μm); however, there was a substantial variation in the released particle concentration depending on a product. The total aerosol mass concentration was dominated by the presence of coarse particles, and it ranged from ∼30 μg/m3 to ∼30,000 μg/m3. The TEM verified the presence of nanoparticles and their agglomerates in liquid and airborne states. The products were found to contain not only Ag and Zn compounds - as advertised on the product labeling - but also a variety of other metals including lithium, strontium, barium, lead, manganese and others. The results presented here can be used as input to model population exposures as well as form a basis for human health effects studies due to the use nanotechnology-enabled products.